Potensi Limbah Kulit Durian sebagai Biopestisida Ramah Lingkungan: Penelitian - Silvia Rahmi Ekasari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Plant Pest Organisms (OPT) are one of the limiting factors in efforts to increase agricultural production. One alternative that can be used in this protection activity is environmentally friendly biopesticide from durian skin waste. The active ingredients contained in durian skin include flavonoids, polyphenols, and saponins which are toxic to pests and mosquitoes so that durian skin biopesticides can be used to replace the role of synthetic pesticides. In addition, durian skin also has very important benefits for human health because it contains lignin and cellulose which are good for health. The potential of durian skin waste is very good if used by biopesticide businesses considering that the materials used are very easy to obtain and the costs incurred are also cheap. The limited knowledge of the community regarding the potential of durian skin waste results in a lot of waste being thrown away. So a simple durian skin waste processing technique is needed into biopesticides. Durian skin waste biopesticide has proven effective in killing chili plant pests, peach aphids, fruit flies, armyworms, Aedes aegepty mosquitoes, and American cockroaches.